Role of ferric and ferrous ions in the enhancement of the heterogeneous solar photocatalytic degradation of combined mixture of chlorophenols - Abeish, Abdul Basit Mohamad S; Ang, Ming; Znad, Hussein (I W A Publishing, 2015)
The solar-photocatalytic degradation of 4-Chlorophenol (4-CP) and 2,4-Dichlorophenol (2,4-DCP) was investigated individually and combined in the presence of Fe2+ and Fe3+ ions. The results revealed that both Fe2+ and Fe3+ ions enhanced the heterogeneous photocatalytic degradation potentially. Fe3+ ions rapidly converted to Fe2+ ions as soon as the irradiation started. The intermediates formed during the degradation of 4-CP/2,4-DCP were also monitored and identified. Three main intermediates were observed, hydroquinone (HQ),phenol (Ph), and 4-chlorocatechol (4-cCat) with traces of benzoquinone (BQ). The results support a new trend of research by utilizing other cheap iron ions sources in the photocataltyic degradation.